Kepemimpinan Perempuan Dalam Jabatan Publik (Studi Kasus Pada Kantor Kecamatan Pangkajene Dan Kepulauan) - Afriani, Afriani; Malik, Ihyani; Madani, Muhlis (Universitas Muhammadiyah Makassar, 2021)
ABSTRACT This study aimed to describe women's leadership in public positions at the District Office of Pangkajene and Islands. This study used a descriptive qualitative type of research. This study used data observation, interviews, documentation. The number of informants in this study were 7 people. The results showed that (1) the female leader as the mother had been carried out well, namely the leaders always accepted the complaints of her staff, (2) the female leader as a sexual object or a good motivator had been going well because the staff were able to work without being ordered to.(3) The female leader as a favorite, it was proven to exist because the staff made the section head , (4) The female leader as an iron woman was in the leadership of the section head seen from those who were firm to their staff in order to provide good discipline.